COUPLING AMPULLINID GASTROPODS: SEXUAL BEHAVIOUR FROZEN IN PALAEOGENE DEPOSITS OF NORTHERN ITALY (Rivista italiana di Paleontologia e Stratigrafia, 2008)
Couples of the ampullinid gastropods Globularia (Eocernina) vulcani (Brogniart, 1823), Amaurellina (Crommium) angustata (Grateloup, 1827) and Amaurellina (Pachycrommium) cf. suessoniensis (d'Orbigny, 1850), composed of dimorphed shells tightly conjoined at the apertures, from the Palaeogene (Eocene and Oligocene) marine successions of northern Italy, are interpreted as buried while mating, specimens being "frozen" while suddenly covered by a mass of sediment. Violent depositional events were responsible for their rapid burial, primarily by volcanoclastics, the formation of which had also involved acidification. The consequent poisoning of sea water and/or overwarming beyond the range in which the gastropods could survive, induced mass mortality. A similar set of conditional circumstances is also discussed for differently sized coupled specimens of Ampullinopsis crassatina (Lamarck, 1804), preserved with their shells slightly apart but with their apertures almost in contact. With reference to the catastrophic eruption of Vesuvius in A.D. 79, when Pompei was buried under tephra, it is thought that volcanic activity caused the death and burial of all these pairing gastropods in a "Pompeian" way.